2018
DOI: 10.1364/boe.9.003495
|View full text |Cite
|
Sign up to set email alerts
|

Stability of gel wax based optical scattering phantoms

Abstract: Phantoms with tuneable optical scattering properties are essential in the development and refinement of optical based imaging techniques. Mineral oil based ‘gel wax’ phantoms are the subject of increasing interest due to their ease and speed of manufacture, non-toxic nature, ability to cast into anatomically realistic shapes, as well as their cost-effective nature of production. The addition of scatterers such as titanium dioxide powder and monodisperse silica microspheres to the gel wax allows for the creatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…Additionally, we showed that our material can be reused and remoulded without significantly affecting the acoustic and/or optical properties, which constitutes a further considerable advantage of the fabrication process. Importantly, we did not observe a statistically significant drift over a time frame of almost a year, thereby confirming expectations based on prior observations of longitudinal studies on the stability of oil-based materials [41], [42], [46], [49]. Controllable mechanical robustness in the tissue-mimicking range and high intrinsic stability permit long-term usage of the material in a wide variety of phantom applications, which also has potential for application in biophotonic and ultrasound imaging.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Additionally, we showed that our material can be reused and remoulded without significantly affecting the acoustic and/or optical properties, which constitutes a further considerable advantage of the fabrication process. Importantly, we did not observe a statistically significant drift over a time frame of almost a year, thereby confirming expectations based on prior observations of longitudinal studies on the stability of oil-based materials [41], [42], [46], [49]. Controllable mechanical robustness in the tissue-mimicking range and high intrinsic stability permit long-term usage of the material in a wide variety of phantom applications, which also has potential for application in biophotonic and ultrasound imaging.…”
Section: Discussionsupporting
confidence: 87%
“…Sample thicknesses were determined before each measurement using Vernier callipers. Based on previous reports on a similar material type (gel wax), the scattering anisotropy factor (g) was taken to be g = 0.7 and the refractive index n = 1.4 [41]. Three measurements at distinct positions on the sample were taken in a wavelength range of 450 to 900 nm.…”
Section: Optical Characterizationmentioning
confidence: 99%
“…Thermoplastic elastomers are composed of a rigid phase made of styrene structures and a rubber phase made of elastomeric structures and are easily processable as a melt at elevated temperatures 168 . Oil-based materials can be purchased off the shelf in the form of 'gel wax' [169][170][171] or can be manufactured from a choice of polymers and oil, where SEBS and mineral oil have proven popular [172][173][174] . The fabrication procedure typically requires sonication of additives with the plasticizer, mixing with the polymer and heating to the respective melting temperature, before degassing and curing.…”
Section: Non-water-based Materialsmentioning
confidence: 99%
“…Oil-based materials are nontoxic, cost-effective, readily available, mechanically robust, have excellent temporal stability and short curing times 174,175 . Depending on their formulation, copolymer-in-oil materials can be optically transparent 169,176 with scattering and absorbing properties tuneable by additives such as oil-based dyes 169 and metal oxide powders 169,171 . The mechanical and acoustic properties are similar to breast fat 173 and can be modified by variation of polymer concentration 173,174 , polymer 173 or plasticizer 174 type.…”
Section: Non-water-based Materialsmentioning
confidence: 99%
“…However, there is currently no general consensus on a unitary standard for cross-platform implementation, as each solution presents drawbacks that are more or less important in one context or the other. Some materials are rather unstable (agarose, in terms of dehydration, biological contamination and smearing of dyed inserts [21], or gel wax, which softens below 60°C), some entail harsh processing conditions that may be incompatible with (bio)dyes (PVCP) or provide heterogeneous texture (freeze-thawn aqueous PVA [26]), some require the addition of exogenous (micro)scatterers that may suffer from flocculation or sedimentation (PVCP, gel wax [32]), some are incompatible with lipophilic dyes (agarose, chitosan, freeze-thawn aqueous PVA), some with hydrophilic dyes (PVCP, gel wax), and the potential to encode anatomical micro or hierarchical structures remains a general issue. In a recent paper [33], we contributed to test the use of an ubiquitous elastomer as polydimethylsiloxane (PDMS).…”
Section: Introductionmentioning
confidence: 99%